Escola, poder e formação: um modelo micropolítico de análise - Virgílio Silva Rego da (Universidade do Minho, 2004)
This text shows the results of a research, in a sociological and organizational perspective, accomplished at the Galécia Secondary School (a confidential denomination) and with the focus on school-based training problematic(s). It introduces a theoretical approach in which we define a model that articulates the teachers and other educators continuous training questions with the micropolitical perspective, acquiring a great importance concepts like power, leadership, "voice, exit and loyalty", regulation, and so on. Through this case study, we conclude that school has a tendency to be considered as a place of training production, as a result of a "dispersed leadership" exercise, double facilitative in a picture of "autonomous regulation" with reference to training. This research also allows the conclusion that the training practices on Galécia Secondary School contributed to prevalent of a restricted emancipation and of an allowed domination.